Status Hukum Tanah Hak Milik bagi Ahli Waris yang Pindah Kewarganegaraan Menjadi Warga Negara Asing - Agnes Geraldine Olga Supriyana; I Nyoman Putu Budiartha; I Ketut Sukadana (Jurnal Interpretasi Hukum, 2020)
Indonesian citizens who have transferred citizenship due to mixed marriages with other citizens who obtain property rights due to inheritance should be obliged to relinquish this right within one year. If it is not released then the right is lost because the law and the land fall to the state. However, in reality some of these property rights have not been released. This research is formulated to determine the status of land ownership rights that are not released by heirs who become foreign nationals and to find out the legal efforts taken by heirs who have transferred citizenship to become foreign citizens in releasing their ownership rights over land acquired due to inheritance. The research method used in this research is normative legal research method. The results showed that the status of land ownership rights that were not released by heirs who became foreign citizens was lost due to the law. This occurs after a period of one year, and the land becomes State land. Then, the legal effort made by the heirs in releasing ownership rights over the land obtained due to inheritance is to apply for more Indonesian citizenship or to remain a foreign citizen residing in Indonesia, so after one year they can obtain use rights or transfer of property rights. It can be done through buying and selling.